Highly recoverable TiO2–GO nanocomposites for stormwater disinfection. (1st May 2016) - Wang, Gen; Feng, Wenjun; Zeng, Xiangkang; Wang, Zhouyou; Feng, Chuanping; McCarthy, David T.; Deletic, Ana; Zhang, Xiwang
Abstract: A highly recoverable titanium dioxide-graphene oxide (TiO2 –GO) composite was developed by a facile method of ultrasonic treatment of GO nanosheets and TiO2 nanoparticles, which should overcome the separation problem of nanosized TiO2 from treated water. Separability of the prepared samples was systematically investigated by gravity settling experiments. The samples' photocatalytic activity for stormwater disinfection was also studied under the irradiation of a solar simulator. The results demonstrated that TiO2 –GO showed high efficient separability due to its accelerated settling behaviour. Zeta-potential analysis showed that the accelerated sedimentation of the catalyst was attributed to the aggregation of TiO2 –GO resulting from the electrostatic attraction between TiO2 and GO. The TiO2 –GO composite with a mass ratio of 100:2 (TiO2 -2%GO) achieved both higher separability and good photocatalytic activity for stormwater disinfection. Its suspension became clear (turbidity < 50 NTU) after 8 h of sedimentation, while 99.5% of E.coli were deactivated in 90 min. The TiO2 –GO composite exhibited excellent durability; no apparent change in the separability of TiO2 -2%GO was observed after 10 treatment cycles (15 h in total), while only slight decrease in the photocatalytic activity was noted. In conclusion, the developed TiO2 –GO composite showed promising results for stormwater disinfection. Graphical abstract: Highlights: Highly recoverable TiO2 –GO composites were developed. The separation of TiO2 –GO was realized in terms of accelerated sedimentation. TiO2 –GO had high performance in stormwater disinfection under solar light irradiation. TiO2 –GO exhibited excellent durability for stormwater disinfection.